Gulf X-linked hypophosphatemia preceptorship: July 4–6, 2019, Bicêtre Paris sud hospital, Paris, France - Alsaffar, Hussain; Beshyah, Salem (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
X-linked hypophosphatemia (XLH) is an inherited disorder characterized by low levels of phosphate in the blood. Phosphate levels are low because phosphate is abnormally processed in the kidneys, which causes urinary phosphate wasting and leads to rickets in the young patients and osteomalacia in adults in addition to several other complications thereof. A 3-day conference was hosted by the Rare Diseases Unit of the Bicetre Paris Sud Hospital on July 4–6, 2019. Presentations covered the subject in a comprehensive manner spanning physiology, clinical presentations, disease burden, and the latest in the management of the XLH and its musculoskeletal, neurosurgical, obstetric, and other complications in both children and adults. Several illustrative and challenging cases were presented and discussed. The authors attended the event and would like to present a personal perspective to highlight the proceeding of the conference to extend the benefit to others who did not attend it.
Keywords: Bone deformities; bone disorders; congenital and genetic diseases; endocrine diseases; fracture; kidney and urinary diseases; rickets; short stature; X-linked hypophosphatemia; X-linked hypophosphatemic rickets